Algorithm for Excitation Optimization of Fabry–Pérot Filters Used in Swept Sources - Avanaki, Mohammad R. N. (2019)
We investigate the improvement in the nonlinearity of a conventional wavelength swept laser source on the basis of a fiber Fabry-Pérot tunable filter using a well-established optimization method, simulated annealing (SA). The signal driving the filter is constructed from many short ramps of different slopes that are interconnected. The values of the slopes are optimized through the SA algorithm to achieve maximum amplitude for the Fourier transformed peaks of the photodetected interferometric signal.